The transcription factor VvWRKY33 is involved in the regulation of grapevine (Vitis vinifera) defense against the oomycete pathogen Plasmopara viticola - Merz, Patrick; Höll, Janine; Bogs, Jochen (Physiologia plantarum, 2015)
Grapevine (Vitis vinifera ssp. vinifera) is one of the most important fruit species; however, it is highly susceptible to various pathogens, which can cause severe crop losses in viticulture.
First published: 06 August 2014
Gesehen am 29.05.2020